2023
DOI: 10.32792/utq/utjsci/v10i1.919
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of blaCTX-M, blaTEM Genes in  Bacteria Isolated From Bladder Cancer Patients with UTI

Huda Jassim,
Yahya A. Abbas Alkhafaji,
Hazim R.Alkafaji

Abstract: Urinary tract infections (UTIs) are among the most prevalent infections in cancer patients . Two hundred urine samples were taken from patients with bladder cancer between the dates of 1 April 2021 and 15 October 2021 while they were enrolled in third floor Ghazi Al- Hariri Hospital, Medical City, Baghdad Province, and private clinics in Nasiriyah Province (100 from patients treated with MMC and 100 from patients treated with BCG). Forty urine samples were taken from patients with UTI without Bladder Ca (contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…In current study, the frequency of positive cultures for microorganisms isolated from urine samples (90%). The results in present study in accordance with previous studies in Ethiopia [26], and convergence with other studies [27] and [28].The finding is higher than reported conducted in Baghdad city, Iraq [29] and Italy [30]. The differences could be attributed to geographical variations where the studies conducted as well as sample size, sanitation status, educational level, awareness, community customs and sexual traditions [29].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In current study, the frequency of positive cultures for microorganisms isolated from urine samples (90%). The results in present study in accordance with previous studies in Ethiopia [26], and convergence with other studies [27] and [28].The finding is higher than reported conducted in Baghdad city, Iraq [29] and Italy [30]. The differences could be attributed to geographical variations where the studies conducted as well as sample size, sanitation status, educational level, awareness, community customs and sexual traditions [29].…”
Section: Discussionsupporting
confidence: 91%
“…However, their effectiveness relies on susceptibility of pathogenic bacteria. Therefore, understanding bacterial susceptibility patterns to antibiotics is critical for management of all types of bacterial infections [28]. In our study, both gram positive and gram-negative bacteria isolated were resistant to different classes of antibiotics.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In our study, it was found that Klebsiella pneumoniae was as an opportunistic multidrug-resistant bacteria(MDR). Some genes for the resistance enzymes bla CTX-M and bla TEM were detected in these bacteria by PCR [23].…”
Section: Discussionmentioning
confidence: 99%